Factors Affecting Improved Performance for Sustaining Sub-District Welfare: Village leaders in Java Island, Indonesia - DWI MARDIANA SUSILAWATI, 090210372/L (Hunan Daxue/Hunan University, 2021)
In the current Reform Era, performance is one of the most important issues discussed among the academic community and bureaucratic institutions. This study aims to analyze the influence of servant leadership, motivation, competence, work environment, and perceptions of the delegation of authority on the performance of the head of District East Java, Indonesia, the role of motivation in weighing these factors in improving performance. This research is a type of causal research with a population of 300. In the sample determination, a purposive sampling technique was used. Two hundred samples were obtained from all members of the village in East Java. Multiple regression analysis is used in this research with Statistics Software as a data processing tool. The results in this study are servant leadership, competence; the work environment has a positive and significant effect on the performance of the sub-district head, while motivation and perceptions of the delegation of authority have no significant effect on the performance of the sub-district head in East Java, Indonesia. For becoming a sustainable green village, one's competence and loyalty are needed so that the performance achievement target is achieved so that this research becomes a reference in developing small villages throughout the archipelago, especially East Java. This research is very limited in only a small scope of one village, so future research can reexamine the role of technology such as a pandemic as it is now.